Driving Meaningful Innovation for Human Resources in the Public Sector: A Systematic Literature Review - Abdul Rahman; Fahdiansyah Putra; Shelda Adriana Taimaris Rogi (Institut Pemerintahan Dalam Negeri, 2026)
Human resource innovation in the public sector is crucial for organizational adaptability and resilience, yet knowledge on how to foster meaningful innovation remains limited. This study aims to answer the question: how can we drive meaningful innovation in human resources in the public sector? Using the Systematic Literature Review (SLR) method, this study extracted a total of 1,190 Scopus articles and identified 24 relevant and high-quality articles from the Scopus database (2016–2026) for further analysis. The analysis identified four main, systemically interrelated themes to foster human resource innovation in the public sector. First, leadership that builds a safe psychological climate and a culture of innovation. Second, human-centered human resource management practices, particularly recognition, inclusion, locally specific training, innovation standards in performance evaluation, and the creation of new roles. Third, employee psychological capacity and internal motivation, including proactive motivation, paradox mindset, and compassion. Fourth, equitable digital governance, where human resources information system and human resource analytics technologies are complementary and only meaningful if supported by capabilities, motivation, opportunities, and guarantees of algorithmic fairness. The conclusions of this study confirm that meaningful public human resource innovation is not generated by a single factor, but rather by the systemic interaction between these four pillars. Consequently, public leaders need to shift their focus from rigid procedures to human empowerment, and ensure that every innovation intervention is holistic and contextual.